Cathepsin S is the major activator of the psoriasis-associated proinflammatory cytokine IL-36γ - Ainscough, Joseph S. (Proc Natl Acad Sci U S A, 2017)
The proinflammatory cytokine IL-36γ is highly expressed in epithelial cells and is a pivotal mediator of epithelial inflammation. In particular, IL-36γ is strongly associated with the inflammatory skin disease psoriasis. As with other IL-1 cytokines, IL-36γ is expressed as an inactive precursor and must be processed by specific proteases to become bioactive. Our aim therefore was to identify protease/s capable of IL-36γ activation and explore the importance of this activation in psoriasis. Using a keratinocyte-based activity assay in conjunction with small-molecule inhibitors and siRNA gene silencing, cathepsin S was identified as the major IL-36γ–activating protease expressed by epithelial cells. Interestingly, cathepsin S activity was strongly up-regulated in samples extracted from psoriasis patients relative to healthy controls. In addition, IL-36γ–Ser18, identified as the main product of cathepsin S-dependent IL-36γ cleavage, induced psoriasiform changes in human skin-equivalent models. Together, these data provide important mechanistic insights into the activation of IL-36γ and highlight that cathepsin S-mediated activation of IL-36γ may be important in the development of numerous IL-36γ–driven pathologies, in addition to psoriasis.